The Role of Growth Mindset in Public Policy Development and Community Empowerment: A Critical Literature Review - Nur Fajri (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2022)
Background of the problem: As social conditions change and governance problems become more complicated, it is more important than ever for institutions and communities to be able to adapt, learn, and come up with new ideas. The idea of a growth mindset, which is the belief that you can improve your skills and outcomes by working hard and learning, has been studied a lot in schools and psychology. However, its relevance to public policy and community development has not been studied as much. Purpose: The goal of this study is to critically look at how the idea of a growth mindset has been thought about, used, or suggested in the areas of public administration and community empowerment. Method: This study looked at 68 scholarly sources published between 2010 and 2025 using a critical literature review method. Result: The results show three main ideas: (1) a growth mindset helps institutions learn and come up with new policies; (2) it gives people more power and encourages them to get involved, especially in places where they are not normally involved; and (3) it uses in public settings is still not well-defined or well-researched. Implication: The research adds to the theoretical integration of psychological concepts into discussions about governance and development by providing a micro-level perspective to go along with structural and institutional analyses. In practice, it shows how mindset-based interventions can help make public systems more adaptable, inclusive, and strong, if they are used with an eye on context and fairness. This study shows that we need more real-world research, frameworks that cross disciplines, and critical thinking about how mindset affects public life.